A Web-based Tool for Supporting the Management of Outreach Projects and Programs in the University: A Group-based Expert Walkthrough Evaluation - Dalepiane, Igor; Fell, Lucas; Fialho, Matheus; Mello, Aline; Basso, Fábio; Bernardino, Maicon (Anais do Simpósio Brasileiro de Informática na Educação (SBIE), 2024)
Due to Resolution Nº 7 of 2018 by the National Council of Education (CNE) of Brazil, outreach curricularization is mandatory since 2023. This study aims to evaluate the usability of our tool, which is designed to support the management of academic outreach activities, projects and programs. A Groupbased Expert Walkthrough was conducted with potential users from our university’s academic community. The goal is present our proposal web-based tool as well as how we evaluating the usability in our tool, while allowing subjects to offer suggestions for improvements and new ideas. Valuable qualitative feedback was obtained, guiding the development of the tool, prioritizing and validating requirements. The usability evaluation provided insights to enhance the tool’s learnability and user-friendliness for the academic community.